USAHA PEMENANGAN HARRIS-ZARDEWAN PADA PILKADA DI KECAMATAN UKUI KABUPATEN PELALAWAN TAHUN 2015 (SEBUAH STUDI KOMUNIKASI POLITIK) - Rifai, Moch Erif; Tinov, M. Y. Tiyas (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
In the Pelalawan Regional Election 2015, were won by Harris-Zardewan with a total of 68.618 votes, the writer found an interesting phenomenon, the most votes which got by Harris-Zardewan in district Langgam and Ukui which reaching 3.560 and 2.823 votes. The large votes that gained by Harris-Zardewan which that happen in district Langgam considered reasonable, due to the fact that district Langgam is the candidate's origin, Harris. However, But the quite large vote in district Ukui were questioning. This study aims to know what mechanisms and strategies of political communication patterns conducted by Harris-Zardewan to gained large votes in district Ukui.The method that the writer used in this research is qualitative method. There were 8 respondent in this research, consisting Pelalawan Election Commission secretary, Harris-Zardewan winning team, representatives of community organizations and representatives of the community. The data in this research was collected by interview and documentation. Then the data processed by using qualitative methods.From the research, the writer concluded that political communication mechanism strategy that used by Harris-Zardewan is by using their last period in their duty to being closer to Pelalawan Region people, especially in district Ukui. Therefore, their political communication pattern that used by Harris-Zardewan was direct and open campaign to Pelalawan Region people, in district Ukui, open discussion, and formal visits as incumbent in this regional election.Keywords: Communication Strategy, Regional Election, Political Communication